Comparison of solar photovoltaic module temperature models - Jakhrani, A.Q.; Othman, A.K.; Rigit, A.R.H.; Samo, S.R. (IDOSI Publication, 2011)
This paper presents the comparative study of the different models that used to predict the solar photovoltaic module temperature, which is one of the most important factors responsible for lowering the performance of photovoltaic modules. The approach of the different models was examined in order to evaluate the estimated behavior of module temperature increase with respect to ambient temperature and solar radiation. A total of 16 models have been reviewed by employing monthly mean daily meteological data of Kuching, Sarawak. The most models showed similar trend of increase or decrease of sola photovoltaic module temperature due variation of solar radiation intersity. However, the results of reviewed models were quite different under constant solar radiation and ambient temperature conditions. It was found that the variation in the results was due to the use of different variables, climatic conditions, configuration of photovoltaic modules and the approach used by various researchers in the models.